THE BOOK OF JOB AS A DEPICTION OF A PERSON’S SPIRITUAL BIRTH PROCESS - Shelkovaya, Natalya V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2019)
The article focuses on the eternal theme of human life: suffering and its cause, deeply revealed in the biblical Book of Job. Although from ancient times this problem and its disclosure were interpreted both in philosophy and in religion, it has remained unresolved until nowadays and therefore worries a lot of people. Researchers of the Book of Job focus on two problems: the problem of suffering and the problem of theodicy, which arises from the existence of evil and injustice in the world. However, according to the author of the article, the main idea of the Book of Job is not the problem of God’s justice, but the problem of a person’s spiritual birth. In the text of the article, the author, scrupulously analyzing every image and symbol of the Book of Job, shows and proves that the suffering sent by God to Job through Satan is an initiation through which the transformation of the Job psyche and his spiritual birth takes place. To prove this, the author analyzes the spiritual world-attitude and God-attitude of Job before the trials (God-fearing and law-abiding, life near God) and after the trial (deep vision and feeling of God’s wisdom and all His deeds, life in God and with God). The main author’s method is searching for images and symbols’ disclosure in the Book of Job, not only verbal, but also numerical ones. The article researches the main symbols of the Book of Job and their significance for understanding of this text. The author focuses on the ideas of numbers 3, 7, 10 and especially on the significance of number 10 as some kind of completeness. The author also analyzes the symbolic meaning of the ashes, images of the Leviathan and the Hippopotamus, and Satan as the messenger of God for human trials. The author reveales some key features of human psychology: the role of fear in the human life (Job’s fear of the fate of his sons), behaviour in an extreme situation (Job and his wife), and abandonment of the miserable man (friends and relatives of Job). Based on the disclosure of the symbolism of images and numbers, the author concludes that the problem of justice in the Book of Job is removed. God gives to everyone what he deserves, and suffering and deprivation are not a punishment, not ends in themselves, as in asceticism, but a means of spiritual and mental transformation and spiritual development of person.